2023
DOI: 10.1002/nafm.10856
|View full text |Cite
|
Sign up to set email alerts
|

Catch‐and‐Release Angling Effects on Lake Sturgeon in Wisconsin, USA

Abstract: Discard mortality is an important factor to consider when managing catch-and-release fisheries. Even low levels of discard mortality can induce population-level effects particularly in long-lived, low-productivity species like Lake Sturgeon Acipenser fulvescens. Unfortunately, little is known about the effects of catch-and-release angling on Lake Sturgeon physiology and probability of discard mortality. We used controlled angling events with standardized gear to capture 96 Lake Sturgeon from August to October … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
2
0
0
Order By: Relevance
“…Detection range was estimated during preliminary range testing that was conducted prior to this study, with maximum ranges estimated at approximately 200-250 m (D. A. Gravenhof, unpublished data). Other studies have reported similar ranges, with 100% detection coverage at 100 m (Shaw et al 2023) and maximum ranges of 150-200 m (Tsitrin et al 2022). These passive receivers were each powered by one 3.6-V lithium D-cell battery with a battery life of approximately 8 months.…”
Section: Passive Tracking Of Chinook Salmon and Analysissupporting
confidence: 63%
See 1 more Smart Citation
“…Detection range was estimated during preliminary range testing that was conducted prior to this study, with maximum ranges estimated at approximately 200-250 m (D. A. Gravenhof, unpublished data). Other studies have reported similar ranges, with 100% detection coverage at 100 m (Shaw et al 2023) and maximum ranges of 150-200 m (Tsitrin et al 2022). These passive receivers were each powered by one 3.6-V lithium D-cell battery with a battery life of approximately 8 months.…”
Section: Passive Tracking Of Chinook Salmon and Analysissupporting
confidence: 63%
“…Other studies have reported similar ranges, with 100% detection coverage at 100 m (Shaw et al. 2023) and maximum ranges of 150–200 m (Tsitrin et al. 2022).…”
Section: Methodssupporting
confidence: 54%